Nailbiter. Volume 5, Bound by blood - Williamson, Joshua; Williamson, Joshua; Henderson, Mike, 1981- (Image Comics, 2016)
"Buckaroo, Oregon has given birth to many infamous serial killers, but the worst was the Nailbiter. And now... is it possible he has a daughter? Could Alice's search for the truth about her parentage lead her to origin of the serial killers?"--Amazon.com